Thinking with Black Ecologies in Early Childhood Education - Nxumalo, Fikile; Downey, Correnda; Franklin, Nicole E. (Journal of Childhood Studies, 2024)
We are three Black women working in childhood and youth education research and practice in Tkaronto, Canada. In this paper we bring together our personal, research, and pedagogical inquiries into Black ecologies. We focus on foregrounding how Black ecologies can bring possibilities to (re)story Black nature relations and respond to socio-ecological injustice. Our intention is to encourage early childhood educators to think, in situated ways, with both the potential and challenges of this work. We do this by intentionally foregrounding propositions, grounded in stories and questions for inquiry, that educators can think with in their own contexts.